Distinctive phenotype for HLA-E- versus HLA-A2-restricted memory CD8 αβT cells in the course of HCMV infection discloses features shared with NKG2C+CD57+NK and δ2-γδT cell subsets - Rousselière, Amélie; Gérard, Nathalie; Delbos, Laurence; Guérif, Pierrick; Giral, Magali; Bressollette-Bodin, Céline; Charreau, Béatrice (Frontiers in Immunology, 2022)
The human cytomegalovirus (HCMV) triggers both innate and adaptive immune responses, including protective CD8+ αβT cells (CD8T) that contributes to the control of the infection. In addition to CD8T restricted by classical HLA class Ia molecules, HCMV also triggers CD8T recognizing peptides from the HCMV UL40 leader peptide and restricted by HLA-E molecules (HLA-EUL40 CD8T). This study investigated the frequency, phenotype and functions of HLA-EUL40 CD8T in comparison to the immunodominant HLA-A2pp65 CD8T upon acute (primary or secondary infecion) or chronic infection in kidney transplant recipients (KTR) and in seropositive (HCMV+) healthy volunteer (HV) hosts. The frequency of hosts with detected HLA-EUL40 CD8T was similar after a primary infection (24%) and during viral latency in HCMV+ HV (26%) and equal to the frequency of HLA-A2pp65 CD8T cells in both conditions (29%). Both CD8T subsets vary from 0.1% to >30% of total circulating CD8T according to the host. Both HLA-EUL40 and HLA-A2pp65 CD8T display a phenotype specific of CD8+ TEMRA (CD45RA+/CCR7-) but HLA-EUL40 CD8T express distinctive level for CD3, CD8 and CD45RA. Tim3, Lag-3, 4-1BB, and to a lesser extend 2B4 are hallmarks for T cell priming post-primary infection while KLRG1 and Tigit are markers for restimulated and long lived HCMV-specific CD8T responses. These cell markers are equally expressed on HLA-EUL40 and HLA-A2pp65 CD8T. In contrast, CD56 and PD-1 are cell markers discriminating memory HLA-E- from HLA-A2-restricted CD8T. Long lived HLA-EUL40 display higher proliferation rate compared to HLA-A2pp65 CD8T consistent with elevated CD57 expression. Finally, a comparative immunoprofiling indicated that HLA-EUL40 CD8T, divergent from HLA-A2pp65 CD8T, share the expression of CD56, CD57, NKG2C, CD158 and the lack of PD-1 with NKG2C+CD57+ NK and δ2-γδT cells induced in response to HCMV and thus defines a common immunopattern for these subsets.